Designing mouthwash formulations with innovative molecular components to control initial dental erosion in vivo - Pelá, Vinícius Taioqui; de Brito, Mariana Miranda; da Silva, Gustavo Cassalate; Taira, Even Akemi; Ferrari, Carolina Ruis; Ventura, Talita Mendes Oliveira; Thomassian, Larissa Tercilia Grizzo; Henrique-Silva, Flávio; de Souza, Eduardo Pereira; Carlos, Thais Fernanda; Carvalho, Thiago Saads; da Costa Fuentes, Andrea Soares; et al. (Springer Nature, 2024)
ObjectiveThis study aimed to examine and compare the efficacy of mouthwashes containing different proteins and peptide on the prevention of enamel erosion in vivo, as well as to evaluate the participants’ satisfaction with the formulations.MethodsTwelve participants were selected and underwent five cross-over mouthwash phases: Water (control); 0.1 mg/mL CaneCPI-5; 0.5 mg/mL MaquiCPI-3; 0.1 mg/mL CsinCPI-2; and 0.037 mg/mL Stn15pSpS. After prophylaxis, the participants rinsed (1 min), followed by the acquired enamel pellicle (AEP) formation (2 h). An erosive challenge was made (biopsy, citric acid 1%, 15s) on the buccal surface of the central maxillary incisors. The Relative Surface Reflection Intensity (%SRI) was assessed and analyzed by ANOVA/Tukey’s tests. The calcium release in acid was measured by the Arsenazo method and verified by Kruskal-Wallis/Dunn’s tests. The Spearman’s correlation was used between analyses. A questionnaire evaluated the satisfaction of participants.ResultsFor both analyses, the results showed that mouthwashes containing the proteins or peptide were significantly more effective in preventing enamel erosion compared to deionized water, with no significant differences among the active ingredients (p < 0.05). Also, there was a significant negative correlation between %SRI and calcium released (r=-0.5754). The questionnaire revealed that the volunteers were satisfied with the taste of the products. In addition, the experimental procedures were well tolerable, and no side effects were reported.ConclusionAll mouthwashes containing proteins or peptide were acceptable and effective in protecting enamel against initial dental erosion in vivo. Clinical significance: This study highlights the potential of these pioneer organic components for the development of mouthwashes designed for people with risk of erosive tooth wear.